Image analysis for a microfluidic paper-based analytical device using the CIE L*a*b* color system. Issue 24 (10th November 2016) - Komatsu, Takeshi; Mohammadi, Saeed; Busa, Lori Shayne Alamo; Maeki, Masatoshi; Ishida, Akihiko; Tani, Hirofumi; Tokeshi, Manabu
Abstract : A quantitative method based on image analysis of multiple color changes in microfluidic paper-based analytical devices using CIE L * a * b * color difference is presented. Abstract : The combination of a microfluidic paper-based analytical device (μPAD) and digital image analysis is widely used for quantitative analysis with μPADs because of its easy and simple operation. Herein, we have demonstrated a quantitative analysis based on multiple color changes on a μPAD. The CIE L * a * b * color system was employed to analyse the digital images obtained with the μPAD. We made pH measurements using a universal pH-indicator showing multiple color changes for various pH values of aqueous test solutions. The detectable pH range of this method was wider than the typical grayscale-based image analysis, and we succeeded in the measurements for a wide pH range of 2–9.